Resistensi Mahasiswa terhadap Kebijakan Kampus di UIN Sunan Kalijaga Yogyakarta - Suliadi Suliadi (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2014)
The student resistance to the authority is a history that cannot be separated from the long journey of each country. Student involvement in the process of changes for their nation in every movement of history cannot be denied. Students as intellectual get a job to be responsible for the social and economic situation of the political nation. History has many notes that the changes in social systems, economics, and politics in many countries are the outcome of the intellectuals that was pioneered by the students. Role of students in Indonesia is not a stranger within each change. The achievement of the independence of Indonesia cannot be separated from the role of students who at the time as one of the component of who participated inside. Various resistances of students against the college policy has always colored the dynamics of college life, this is what later became the base of growing various movement organizations in Yogyakarta, even in the progress up to now only UIN, which still survive dialectical process of the student movement. That is the background theme of this research. The research was done at UIN Sunan Kalijaga Yogyakarta. This study uses Michel Foucault’s theory of power relations and knowledge, as well as his theory of resistances JC scott. The method used is a descriptive of qualitative, while the techniques of data collection be done in several ways, namely direct observation (direct observation), participation (direct participation), interview (interview), and document analysis. Techniques of data analysis is started by studying all of the data acquired, reducing the data by creating an abstraction, coding (categorizing data), reconstruction (rearrangements), and fially to do the interpretation ofthe obtained data. The results of this study indicate that the resistances of students at UIN Sunan Kalijaga formed the background by two factors, objective and subjective factors. Objectively factor is the situation of national education that has capitalised and also has affected to the dynamics life in the UIN Sunan Kalijaga. More subjective factors refers to the awareness of students about the role of their social position as a student, as the agents of change and agents of control. A blend of value awareness with objective facts that are inconsistent with expectation later gave birth to resistance. Resistance becomes the biological child of a student combination awareness of the objective situation in education. Meanwhile, a form of resistance has performed by students existing two kinds, in an organized and individually. The organized forms such as: long march action, rector occupation, free speech, as well as publishing leaflts. Whereas resistance is performed by an individual for example: through the articles sent to mass media, mass media both in the form of a daily newspaper and news media students in the internal UIN Sunan Kalijaga Yogyakarta.